Employment adjustment in two countries with poor reputations: Analysis of aggregate, firm, and flow data for Portugal and Germany - Addison, John T. (2005)
This paper supplements aggregate time-series analysis of the speed of employment adjustment with evidence from firm panel and flow data for two countries – Portugal and Germany – sharing unenviable labor market reputations. The Portuguese labor market is often portrayed as terminally inert, while that of Germany as badly ailing. We report broad consistency in the results across data sets in favor of Portugal. In benchmarking Portugal against Germany, the adverse reputation of the former – if not necessarily that of the latter country – may have been exaggerated in contemporary policy debate.